Higher Income and Integration into the Workforce Are the Main Factors Associated with Quality of Life in Acromegalic Patients in Northeastern Brazil - Adriana Maria GuimarãesSá; Pedro Antônio Muniz Ferreira; Marinilde Teles Souza; Gilvan Cortês Nascimento; Sabrina da Silva Pereira Damianse; Viviane Chaves de Carvalho Rocha; Manuel dos Santos Faria; Adalgisa de Souza Paiva Ferreira (International Journal of Endocrinology)
Objective. To identify the factors associated with quality of life in patients with acromegaly with follow-up at the referral service in neuroendocrinology of the state of Maranhão, northeast Brazil. Methods. The Acromegaly Quality of Life Questionnaire (Acro-QoL) was used. Factors independently associated with quality of life were identified using multivariate linear regression, with p values < 0.05 considered significant. Results. The multivariate linear regression analysis indicated a positive association between being integrated into the job market and quality of life scores in the overall domain (β=0.288, p=0.003), psychological domain (β=0.291, p=0.032), and personal relationship domain (β=0.314, p=0.019). We also observed a positive association with income and the quality of life scores in all domains as follows: overall domain (β=0.037, p=0.003), physical domain (β=0.988, p=0.001), psychological domain (β=0.342, p=0.008), physical appearance domain (β=0.270, p=0.049), and personal relationship domain (β=0.315, p=0.012). Conclusion. For patients with acromegaly living in one of the least developed regions of Brazil, integration into the job market and a higher income were associated with a better quality of life.